A taxonomically unique Acinetobacter strain with proteolytic and hemolytic activities recovered from a patient with a soft tissue injury - Almuzara, Marisa (2015)
A taxonomically unique bacterial strain, Acinetobacter sp. A47, has been recovered from several soft tissue samples from a patient undergoing reconstructive surgery owing to a traumatic amputation. The results of 16S rRNA, rpoB, and gyrB gene comparative sequence analyses showed that A47 does not belong to any of the hitherto-known taxa and may represent an as-yet-unknown Acinetobacter species. The recognition of this novel organism contributes to our knowledge of the taxonomic complexity underlying infections caused by Acinetobacter.